A high-strength, environmentally stable, and recyclable starch/PVA organohydrogel electrolyte for flexible all-solid-state supercapacitor. (15th April 2023) - He, Li; Wang, Jinquan; Weng, Sen; Jiang, Xiancai
Abstract: Hydrogel electrolytes have shown great promise in the field of flexible energy storage. However, the conventional hydrogel electrolytes have poor mechanical properties and are not recyclable. In addition, conventional hydrogel electrolytes cannot adapt to low and high temperature operating environments. In this study, starch/PVA/dimethyl sulfoxide/CaCl2 (SPDC) organohydrogel was prepared by the freezing-thawing method. Dimethyl sulfoxide (DMSO) and CaCl2 was introduced to enhance the mechanical properties and widen the working temperature range of the starch/PVA hydrogel. The SPDC organohydrogel had high strength, toughness and good recyclability. The SPDC organohydrogel and the recycled SPDC organohydrogel was used as the electrolyte to assemble the flexible supercapacitor with activated carbon as the electrode. The supercapacitor prepared by SPDC organohydrogel electrolyte exhibited high areal capacitance of 156.50 mF/cm 2 at a current density of 1 mA/cm 2 and high capacitance retention rate of 82.23 % after 8000 cycles of charging and discharging. The supercapacitor prepared by the recycled organohydrogel electrolyte exhibited a high capacitance retention rate of 97.58 %. In addition, the supercapacitor could withstand different angular bending shapes and had wide temperature adaptability from −20 °C to 80 °C. The work provided a new version for the development of "green" hydrogel electrolyte for all-solid-state supercapacitor. Graphical abstract: Unlabelled Image Highlights: Starch/PVA hydrogel were improved by introducing dimethyl sulfoxide and CaCl2 . The SPDC exhibited high mechanical properties, excellent environmental stability and frost resistance. The SPDC showed high recyclability due to the fully physically cross-linked network. The supercapacitor with SPDC as electrolyte delivered high areal capacitance of 156.50 mF/cm 2 at a current density of 1 mA/cm 2 . The supercapacitor with SPDC as electrolyte could be operated over a wide temperature range.